Economic growth and environmental regulation: China's path to a brighter future - Swanson, Timothy M.; Lin, Tun (Routledge explorations in environmental economics, 2009)
chapter 1 Economic growth and environmental regulation in the People’s Republic of China: Introduction to the volume -- part PART I Growth and environmental regulation -- chapter 2 Economic growth and environmental protection in the People’s Republic of China -- chapter 3 Environmental Kuznets Curves in the People’s Republic of China: Turning points and regional differences -- chapter 4 Economic growth and environmental regulation: What is the role of regulation? -- part PART II Growth and environmental management: the PRC’s experiences -- chapter 5 Air pollution control strategy in the People’s Republic of China -- chapter 6 Progress and experience: Water pollution control in the People’s Republic of China -- chapter 7 Strategy report for ecosystem management in the People’s Republic of China’s experience -- part PART III Pathways to a brighter future? International experiences in environmental regulation -- chapter 8 International experiences in air pollution management -- chapter 9 International experience to inform the People’s Republic of China’s water pollution and water resource management policy -- chapter 10 International experiences in ecosystem management -- part PART IV Institutional development for a regulated environment -- chapter 11 Institutional development of environmental management in the People’s Republic of China -- chapter 12 International experiences to inform the People’s Republic of China’s institutional choices for environmental policy -- chapter 13 Recurrent issues in environmental governance -- chapter 14 Conclusion: “The path to a brighter future”.